Subordinated by Culture - Adeyinka A. Aderinto (Nordic Journal of African Studies, 2001)
Women worldwide face discriminations and subordination in the society. This subordination of women is even more pronounced in the developing countries of Asia and Africa. Several scholars (Kenig 1996; Adeyeye 1988; Howard 1985; Kazi 1995; Kumar 1993) have asserted that rural women are discriminated against in terms of employment opportunities, access to social and productive resources, education, health status and family decisions, among others.